Digital Gazetteers: Review and Prospects for Place Name Knowledge Bases - Wijegunarathna KI; Stock K; Jones CB (Association for Computing Machinery, 2026)
Gazetteers typically store data on place names, place types, and the associated coordinates. They play an essential role in disambiguating place names in online geographical information retrieval systems for navigation and mapping, detecting and disambiguating place names in text, and providing coordinates. Currently, there are many gazetteers in use derived from many sources, with no commonly accepted standard for encoding the data. Most gazetteers are also very limited in the extent to which they represent the multiple facets of the named places yet they have potential to assist user search for locations with specific physical, commercial, social, or cultural characteristics. With a focus on understanding digital gazetteer technologies and advancing their future effectiveness for information retrieval, we provide a review of data sources, components, software and data management technologies, data quality and volunteered data, and methods for matching sources that refer to the same real-world places. We highlight the need for future work on richer representation of named places, the temporal evolution of place identity and location, and the development of more effective methods for data integration.
Keywords: Gazetteers; toponyms; place names; geographic information retrieval; information retrieval; geographic databases; geographic information systems